Blood pressure levels and psychosocial stress in students of health sciences. University of Valle, Cali, Colombia, 2003-2004. (Colombia Medica, 2006)
Objective: To evaluate the levels of family stress, social stress and the blood pressure levels in young people and the possible correlation. Materials and methods: A descriptive study was performed recruiting healthy students of health sciences in the University of Valle in Cali, Colombia during 2002-2003. The psychosocial stress inventory included evaluation of the family stress and the evaluation of social stress. The blood pressure was evaluated by physicians using standardized technique with calibrated manual sphygmomanometers. Results: 185 students were recruited with an average age of 21.2±2.6 years old, 178 (96%) were singles, 100 (54%) were women, 173 (93.5%) were of mixed ethnic background, 154 (83.2%) were from middle socioeconomic level (level 3-4). The family dysfunction was observed in 131 (70.8%) students, 66 (35.6%) had high cumulative social changes. The average blood pressure level in all students was normal (106.4/69.7) with high blood pressure levels in males than in females (p< 0.001) associated with the body mass index (p< 0.001) and the black race ( p< 0.02). Family dysfunction was not associated with changes in blood pressure (p=0.80). Social stress was not associated with blood pressure levels (p=0.98). Conclusion: In young people psychosocial stress was high but did not affect blood pressure levels probably due to compensatory physiologic action of vascular endothelium.